Amnion‐Analogous Medical Device for Fetal Membrane Healing: A Preclinical Long‐Term Study. Issue 18 (21st August 2018) - Lee, Jae Yeon; Kim, Hyeonji; Ha, Dong‐Heon; Shin, Jong Chul; Kim, Ahyoung; Ko, Hyun Sun; Cho, Dong‐Woo
Abstract: Although recent invasive fetal surgeries have improved fetal outcomes, fetal membrane rupture remains a major complication, leading to premature delivery, thus undermining the complete benefits of such procedures. A biocompatible amnion‐analogous medical device (AMED) consisting of polycaprolactone framework and decellularized amniotic membrane (dAM)–derived hydrogel for restoration of amniotic membrane defect is developed using 3D printing technology. Its efficacy on healing iatrogenic fetal membrane defects in vitro is evaluated, showing that the dAM gel contains migratory and proliferative properties. The fetoscope feasibility of the developed AMED is assessed using a pregnant swine model. All animals had successfully recovered from anesthesia and the fetoscopic procedure and maintained a healthy condition until the end of the pregnancy. AMED exhibits superior surgical handling characteristics and is easy to manufacture, nonimmunogenic, biocompatible, and suitable for storage and transport for off‐the‐shelf use; hence, it can be used in successfully sealing defect sites, thus improving the preservation of the amniotic fluid, which in turn improves fetal survival and development. Abstract : An amnion‐analogous medical device (AMED), a tissue‐specific ECM‐based 3D‐printed device, can successfully seal defect sites and improve the preservation of the amniotic fluid, which in turn improves fetal survival and development. AMED is a useful tool in the development of therapeutic strategies in fetal membrane reconstruction and other membrane structure organs. These superior handling characteristics exhibit benefits for clinical applications.